Assessing the effects of audiovisual semantic congruency on the perception of a bistable figure - Hsiao, J; Chen, Y; Spence, C; Yeh, S (2012)
Bistable figures provide a fascinating window through which to explore human visual awareness. Here we demonstrate for the first time that the semantic context provided by a background auditory soundtrack (the voice of a young or old female) can modulate an observer's predominant percept while watching the bistable "my wife or my mother-in-law" figure (Experiment 1). The possibility of a response-bias account-that participants simply reported the percept that happened to be congruent with the soundtrack that they were listening to-was excluded in Experiment 2. We further demonstrate that this crossmodal semantic effect was additive with the manipulation of participants' visual fixation (Experiment 3), while it interacted with participants' voluntary attention (Experiment 4). These results indicate that audiovisual semantic congruency constrains the visual processing that gives rise to the conscious perception of bistable visual figures. Crossmodal semantic context therefore provides an important mechanism contributing to the emergence of visual awareness. © 2012 Elsevier Inc.